Correlation of Ultrasonographically Measured Splenic Size with Endoscopic Grading of Esophageal Varices in Cirrhosis of Liver (Bangladesh Critical Care Journal, 2022)
Background: Cirrhosis is the end stage of chronic liver disease, resulting in formation of fibrous tissue, derangement of liver architecture and ultimately results in portal hypertension and its complication.Objective: To find out the correlation between splenic size and endoscopic grading of esophageal varices in diagnosed cases of cirrhosis of liver.Methods: This prospective observational cross-sectional study was carried out in the Department of Radiology and Imaging in collaboration with GHPD, BIRDEM, Dhaka. 110 liver cirrhosis patients with or without esophageal varices diagnosed by endoscopy of UGIT referred to the department of Radiology and Imaging were included in this study on the basis of selection criteria.Result: The following observations and results were obtained in this study the mean age was 44.81 (±14.42) years, minimum age was 18 years and maximum age was 65 years. Majority 69% were male and 31% were female. Esophageal variceal grading of the study population majority 47(42.73%) were grade I, 24(21.82%) were grade II, 16(14.55%) were grade III, 12(10.91%) were grade IV and 11(10%) were no varices. Splenic size by ultrasonography, majority 66(60%) were 12-14.9 cm, 37(33.64%) were ≥15 cm and 07(6.36%) were < 12 cm. In splenic size ≤ 15 cm, grading of esophageal varices, 15.07% had no varices, 60.27% had grade I, 20.55% had grade II, 2.74% had grade III and 1.37% had grade IV. In splenic size ≥ 15 cm grading of esophageal varices, 8.11% had grade I, 24.32% had grade II, 37.84% had grade III and 29.73% had grade IV. That means there is a positive correlation between ultrasonographically measured splenic size and endoscopic grading of esophageal varices in liver cirrhosis patients.Conclusion: Positive correlation was found between ultrasonographically measured splenic size with endoscopic grading of esophageal varices.Bangladesh Crit Care J March 2022; 10 (1): 57-61